1983
DOI: 10.1136/ard.42.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Gangrene developing after minor surgery in a patient with undiagnosed systemic lupus erythematosus and lupus anticoagulant.

Abstract: (homogeneous), DNA binding 52% (normal less than 25 %), IgG 210 IU/ml (normal 128-199 IU/ml), IgA 330 IU/ml (normal 99-181 IU/ml), IgM 299 IU/ml (normal 60-129 IU/ml), complement 93 mg/dl (normal 104-161 mg/dl), rheumatoid factor titre positive. (SI conversion: IU/ml x 1000 = IU/l; mg/dl x 0 01 = g/l.) Clotting studies showed a prothrombin time 16 seconds (normal 13 seconds), activated partial thromboplastin time 54 seconds (normal 34 seconds), kaolin clotting time 36 seconds (normal 28 seconds), thrombin clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Cheah14 had also reported a 33-year-old Chinese woman presenting with digital gangrene 3 weeks after the diagnosis of SLE. Other case reports have been documented from UK 15 16. There has, however, been no documented report of digital gangrene as the initial manifestation of SLE among African blacks.…”
Section: Introductionmentioning
confidence: 98%
“…Cheah14 had also reported a 33-year-old Chinese woman presenting with digital gangrene 3 weeks after the diagnosis of SLE. Other case reports have been documented from UK 15 16. There has, however, been no documented report of digital gangrene as the initial manifestation of SLE among African blacks.…”
Section: Introductionmentioning
confidence: 98%
“…In one study intermittent claudication together with intra-uterine death was described in association with LAC (7). Jindal et al reported a patient who presented with gangrene of the extremities associated with LAC as the presenting sign of SLE (8). In patient A, with large vessel obstructive disease, LAC was demonstrated without signs of SLE.…”
Section: Patient Cmentioning
confidence: 97%
“…Van der Meer, J.T.M. De Wolf, et al 8 years she had been known in our department with a diagnosis of mixed connective tissue disease (MCTD), based on the presence of polyarthritis, severe Raynaud's phenomenon, recurrent pericarditis, restrictive pulmonary function abnormalities with a decreased diffusion capacity, pulmonary hypertension, esophageal hypotony and a positive test for ANA and anti-nucleoribonucleoprotein (anti-nRNP) antibodies. Tests for anti-ds DNA antibodies had been negative.…”
Section: Patient Bmentioning
confidence: 98%
See 1 more Smart Citation
“…The term 'antiphospholipid antibody syndrome' has been proposed for the clinical features associated with anti phospholipid antibodies [11][12][13]. A variety of dermatolog ical manifestations has been linked to the presence of anti phospholipid antibodies, including livedo reticularis [14][15][16], leg ulcers [17][18][19], necrotizing purpura [20], Sned don' syndrome and livedo vasculitis [21], distal cutaneous ischemia [22], widespread cutaneous necrosis [23,24], peripheral gangrene [25,26], thrombophlebitis [19] and hemorrhage [19]. It has recently been suggested that at least some of these cutaneous manifestations may be early markers of the antiphospholipid antibody syndrome [19].…”
mentioning
confidence: 99%